The effects of installation configuration and solidity on the power generation of a linear cascade wind turbine. Issue 180 (September 2018) - Jafari, S.A.H.; Kwok, K.C.S.; Safaei, F.; Kosasih, B.; Zhao, M.
Abstract: PowerWindow is a Linear Cascade Wind Turbine (LCWT) capable of generating electricity in very low blade speed ratios, which makes it a safe power generator in built environments. The power generation mechanism and aerodynamic performance of PowerWindow were investigated using experimental prototyping and computational fluid dynamic simulations in a previous study. Due to the limited suitable locations for installing the device in grounded configuration, this study investigates elevated and ducted installation configurations. In the elevated configuration PowerWindow is installed on a tower or in between two tall buildings. In ducted configuration it is installed inside a ducted area such as a through-building opening. Aerodynamic performances of the elevated and ducted PowerWindow are investigated and compared, using computational fluid dynamic simulations. It is shown that the coefficient of performance of the ducted PowerWindow with 12% is about 50% higher than the elevated one with 8%. The effect of solidity is also investigated on the flow mechanism and power generation. The results show that increasing solidity results in greater increase in power generation of the ducted configuration compared to the elevated one. This study also investigates effect of increasing solidity on the required pressure gradient and recommends an efficient solidity for each configuration based on the installation circumstances. Highlights: PowerWindow is a modular linear cascade wind turbine which can be a safe power generator for built environments. PowerWindow can operate in two alternative installation configurations: elevated and ducted configurations. Front and rear blades show different contributions in the power generation in elevated and ducted configurations. Increasing solidity results in greater coefficient of performance in both configurations. There is an optimum solidity for PowerWindow in each configuration which further increase will decrease the power generation.